2021
DOI: 10.3127/ajis.v25i0.3203
|View full text |Cite
|
Sign up to set email alerts
|

What’s behind a scratch card? Designing a mobile application using gamification to study customer loyalty: An experimental approach

Abstract: The use of game design elements (often called gamification) by firms to engage the customers has attracted attention in recent times. These game elements contribute to shaping up customer’s motivation and loyalty. Gamification is explored from the lens of both empirical as well as an experimental methodological standpoint. There still lacks substantial evidence that explains how and which types of rewards help to understand the customer's motivation. The study addresses this gap by designing an experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Thus, this study provides insight into the practicality of the OTT platform's new approach, like gamification. A survey by [87] stated that reward was a mediator in the relationship between gamification and motivation (hedonic and utilitarian). Similarly, the current study successfully analyses the mediating role of rewards in the relationship between gamification and user engagement.…”
Section: B Second Part Of the Analysismentioning
confidence: 99%
“…Thus, this study provides insight into the practicality of the OTT platform's new approach, like gamification. A survey by [87] stated that reward was a mediator in the relationship between gamification and motivation (hedonic and utilitarian). Similarly, the current study successfully analyses the mediating role of rewards in the relationship between gamification and user engagement.…”
Section: B Second Part Of the Analysismentioning
confidence: 99%
“…It has been applied in many different contexts including technology acceptance and use (Kunz & Santomier, 2019;Naglis & Bhatiasevi, 2019;Lin, et al, 2020), online consumer behavior (Kaur, et. al., 2016) and gamification (Behl & Pereira, 2021;Krath, et al, 2021). However, as pointed out by Valinatajbahnamiri & Siahtiri (2020), the identification of distractors and inhibitors of flow remains a research gap in the existing literature of IS, marketing and psychology; the authors have suggested individual characteristics to be a potential inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Technology is bringing about dramatic global changes, affecting people's daily lives and employment opportunities (Cascio & Montealegre, 2016). The emergence of gig workers is just an example of the radical changes affecting the labour market (Behl & Pereira, 2021;Cascio & Montealegre, 2016). We define a gig economy as the practice of hiring workers in response to a specific project or need (Behl et al 2022;Behl & Pereira, 2021;Cascio & Montealegre, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of gig workers is just an example of the radical changes affecting the labour market (Behl & Pereira, 2021;Cascio & Montealegre, 2016). We define a gig economy as the practice of hiring workers in response to a specific project or need (Behl et al 2022;Behl & Pereira, 2021;Cascio & Montealegre, 2016). As organizations rapidly adapt to this new work culture, they increasingly rely on the employment of gig workers as the driving force behind such economy.…”
Section: Introductionmentioning
confidence: 99%